Simplified approach for building inventory and seismic damage assessment at the territorial scale: An application for a town in southern Italy. Issue 121 (June 2019) - Polese, Maria; Gaetani d'Aragona, Marco; Prota, Andrea
Abstract: The assemblage of a building inventory is necessary for the evaluation of seismic impact scenarios at the territorial scale. Building inventory, representing the distribution of building vulnerability classes at the territorial scale, could be performed at different levels of detail, depending on the size of the building stock, the territorial unit of analysis and on the adopted vulnerability model. Census-based data are usually employed as primary source for building inventory. A recent advancement towards compilation of regional scale inventories is provided by the interview-based Cartis approach, implemented in Italy within "Territorial themes" Reluis project, financed by the Italian Civil Protection Department. This paper proposes a first comparison of the results in terms of building inventory and the subsequent impact assessment that are obtained using Census (CE) and Cartis-based (CA) data for a town in southern Italy; a probabilistic framework for inventory is applied. Different vulnerability models are adopted and results compared. Moreover, a simple procedure that combines the informative levels present in the two approaches is proposed, allowing a mixed-type inventory from Census and Cartis data (CC) to be used for seismic impact assessment. Results of the application show that the inventory and related damage distribution changes as a function of the method adopted and in relation to the parameters considered for building classification in the vulnerability model. Comparing the impact in terms of a mean value of damage over the entire municipality, d m, calculated for various seismic intensities and starting from CE, CA and CC inventory, it is seen that the CC inventory is generally more conservative with respect to CA and CE for all the vulnerability methods, and a maximum scatter of approximately 45% in terms of d m is obtained for the considered application with one of the vulnerability methods. Highlights: The paper presents simplified methods to assemble building inventory. Initial considered databases for building inventory are census returns and a newly developed interview-based database. First comparison of the results on building inventory and damage assessment obtained using three types of building inventory. Different vulnerability methods are considered for building classification and expected damage calculation. The method is applied for a case study town in southern Italy.